2022
DOI: 10.1136/bmjopen-2021-060276
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in French nursing homes during the second pandemic wave: a mixed-methods cross-sectional study

Abstract: IntroductionFrench nursing homes were deeply affected by the first wave of the COVID-19 pandemic, with 38% of all residents infected and 5% dying. Yet, little was done to prepare these facilities for the second pandemic wave, and subsequent outbreak response strategies largely duplicated what had been done in the spring of 2020, regardless of the unique needs of the care home environment.MethodsA cross-sectional, mixed-methods study using a retrospective, quantitative data from residents of 14 nursing homes be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…This suggests that shortages of these PPE could have played a major role in the spreading of the virus in NH during the first wave. This is in line with former research, which found that FFP2 mask shortages or delayed FFP2 mask implementation were associated with higher odds for COVID-19 cases, hospitalization and mortality in NH [28][29][30]. In Belgium, the first case of COVID-19 was reported on February 4 th , 2020, among a passenger who returned from Wuhan, China.…”
Section: Plos Onesupporting
confidence: 90%
“…This suggests that shortages of these PPE could have played a major role in the spreading of the virus in NH during the first wave. This is in line with former research, which found that FFP2 mask shortages or delayed FFP2 mask implementation were associated with higher odds for COVID-19 cases, hospitalization and mortality in NH [28][29][30]. In Belgium, the first case of COVID-19 was reported on February 4 th , 2020, among a passenger who returned from Wuhan, China.…”
Section: Plos Onesupporting
confidence: 90%
“… * Classification of the location of respondents’ practice based on the DREES map “Proportion of nursing homes affected in wave 1” ( 20 ). ** Chi-2 test.…”
Section: Resultsmentioning
confidence: 99%
“…The aim had been 2-fold: firstly, to comprehend the crisis-induced needs for refined crisis management strategies ( 17 , 18 ) and secondly, to explore the psychological impact during unprecedented circumstances, shedding light on coping mechanisms ( 18 ). This research, conducted post-lockdown, provides crucial insights into vulnerable populations’ experiences ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%